2023
DOI: 10.4103/jisp.jisp_148_22
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-printed vanperio educative dental model – A review report of its chairside evaluation

Abstract: Background: Patient education and demonstration of osseous defects by teachers and clinicians are difficult even though there are different models made up of metal, plastic, plaster, stone, and acrylic. To overcome such difficulty, 3D printed Vanperio model was printed for multifunctional activity. Aims and Objective: The aim of this article was to provide information on the 3D printed VANPERIO model and its implications in the field of periodontics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Addressing alveolar bone defects and restoring bone structures in patient treatment remains a challenging aspect of clinical practice in dentistry. Nevertheless, significant strides have been taken in incorporating scaffolding and 3D-printing technologies into oral and maxillofacial surgery, particularly in the context of periodontal and alveolar bone regeneration [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and in numerous dental applications [38][39][40]. Studies reported in demonstrate successful applications in periodontal and alveolar bone regeneration, with scaffolding technologies, biodegradable constructs, and antibacterial scaffolds showing promising outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing alveolar bone defects and restoring bone structures in patient treatment remains a challenging aspect of clinical practice in dentistry. Nevertheless, significant strides have been taken in incorporating scaffolding and 3D-printing technologies into oral and maxillofacial surgery, particularly in the context of periodontal and alveolar bone regeneration [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and in numerous dental applications [38][39][40]. Studies reported in demonstrate successful applications in periodontal and alveolar bone regeneration, with scaffolding technologies, biodegradable constructs, and antibacterial scaffolds showing promising outcomes.…”
Section: Introductionmentioning
confidence: 99%